2017
DOI: 10.1002/14651858.cd004063.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Palliative chemotherapy and targeted therapies for esophageal and gastroesophageal junction cancer

Abstract: People who receive more chemotherapeutic or targeted therapeutic agents have an increased overall survival compared to people who receive less. These agents, administered as both first-line or second-line treatments, also led to better overall survival than best supportive care. With the exception of ramucirumab, it remains unclear which other individual agents cause the survival benefit. Although treatment-associated toxicities of grade 3 or more occurred more frequently in arms with an additional chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 198 publications
5
103
1
4
Order By: Relevance
“…The use of an unusual treatment regimen may limit opportunities for second-line treatment and subsequent OS benefit. [4][5][6]14 In our study, we found less serious (grade 3-5) toxicity in patients receiving doublets (21%) compared to triplets (33%) as well as similar OS and TTF rates, which supports the shift toward doublet therapy as preferred strategy in these patients. Current national and international guidelines recommend a fluoropyrimidine and platinum doublet in metastatic esophagogastric cancer patients, with the addition of an anthracycline or taxane in selected patients.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The use of an unusual treatment regimen may limit opportunities for second-line treatment and subsequent OS benefit. [4][5][6]14 In our study, we found less serious (grade 3-5) toxicity in patients receiving doublets (21%) compared to triplets (33%) as well as similar OS and TTF rates, which supports the shift toward doublet therapy as preferred strategy in these patients. Current national and international guidelines recommend a fluoropyrimidine and platinum doublet in metastatic esophagogastric cancer patients, with the addition of an anthracycline or taxane in selected patients.…”
Section: Discussionsupporting
confidence: 66%
“…In the curative setting, docetaxel, oxaliplatin and 5-FU/leucovorin (FLOT) showed longer survival in gastric cancer when used as a perioperative regimen as compared to anthracycline triplets. [4][5][6] In addition, grade 3-5 toxicity rate was only marginally lower compared to doublets (18% vs. 21%, respectively). 31 However, in the palliative setting, it remains inconclusive whether first-line taxane triplets or fluoropyrimidine doublets followed by second-line taxanes should be preferred in view of survival benefit and toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Palliative chemotherapy is considered standard treatment because it can improve survival and quality of life in incurable esophagogastric cancer patients. 3,4 Currently, doublet therapy with a fluoropyrimidine and platinum compound is recommended as first-line palliative chemotherapy, providing a survival benefit of several months. 5,6 Unfortunately, chemotherapy often causes toxicity, which may result in dose reductions, suspension, and discontinuation of chemotherapy and can thereby compromise treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%